Effects of phytase supplementation on reproductive performance, apparent total tract digestibility of Ca and P and bone characteristics in gestating and lactating sows - Dal Jang, Young; Lindemann, Merlin D; van Heugten, Eric; Jones, Richard D; Gyun Kim, Beob; Maxwell, Charles V; Radcliffe, J Scott (Revista Colombiana de Ciencias Pecuarias, 2014)
Summary Background: phytase supplementation to sow diets may improve digestibility of P and Ca and bone integrity of suckling piglets. Objective: two experiments were conducted to investigate the effect of phytase supplementation to gestation and lactation diets on reproductive performance, apparent total tract digestibility (ATTD) of P, Ca, and N in sows and bone characteristics in sows and piglets. Methods: in Experiment 1, a multistate study involving 204 sows was conducted at 3 cooperating research stations. Sows were assigned to 1 of 4 treatments at breeding: 1) negative control [low Ca and available P (aP) diet], 2) Treatment 1 plus 300 FTU of supplemental phytase/kg of diet, 3) Treatment 1 plus 600 FTU of supplemental phytase/kg of diet, and 4) positive control (normal Ca and aP diet). In Experiment 2, a total of 16 sows (Yorkshire × Landrace; average parity, 2.3) were randomly allotted to 1 of 3 treatments based on body weight (BW) and parity at d 34 to 52 of gestation. Treatments were: 1) low Ca and aP diet, 2) low Ca and aP diet with 500 FTU of supplemental phytase/kg of diet, and 3) normal Ca and aP diet. Results: in Experiment 1, the number of total born (p < 0.05), live born (p = 0.05), litter weight of live born (p < 0.01) and weaning pigs (p < 0.05) were increased in a quadratic manner by increasing phytase supplementation level up to 300 FTU/kg. There was a linear increase in piglet weaning weight (p < 0.05) by increasing supplemental phytase levels. There were no differences in reproductive performance in Experiment 2 (p > 0.10). In gestation the ATTD of P was lower for the low Ca and aP without phytase group than the normal Ca and aP (p < 0.01) and phytase-supplemented (p < 0.05) groups. The ATTD of Ca in the normal Ca and aP group was higher than that in low Ca and aP without phytase group (p < 0.05). In lactation, the phytase-supplemented group had higher ATTD of P compared with the other groups (p < 0.05) whereas the ATTD of Ca in phytase-supplemented group was higher than that in low Ca and aP without phytase group (p < 0.10). When the digestibility data was pooled for both gestation and lactation periods, the ATTD of P in the phytase-supplemented group was the highest among dietary treatments (p < 0.05). There were no phytase effects on sow bone ash content at weaning, and piglet bone strength and ash content at birth. However, piglets from the phytase-supplemented sows had higher bone strength (p < 0.10) and ash content (p < 0.05) at weaning compared with those from non-phytase sows. There were positive correlations at birth between piglet BW and bone strength (p < 0.01) and between bone strength and ash content (p < 0.001). Additionally, at weaning positive correlations between piglet BW and bone ash content (p < 0.05), between piglet BW and bone strength (p < 0.001), and between bone strength and ash content (p < 0.05) were observed. Conclusion: phytase supplementation from mid-gestation through lactation increased the ATTD of P and Ca both for gestating and lactating sows, improved bone integrity of their progeny, and had potential to increase litter size and performance but did not affect bone characteristics of sows and newborn pigs. Key words: bone traits, exogenous enzyme, nutrient availability, phosphorus, pig. Resumen Antecedentes: la adición de fitasa a la dieta de cerdas puede mejorar la digestibilidad del P y Ca, así como la integridad ósea de los cerdos lactantes. Objetivo: se realizaron dos experimentos para investigar el efecto de la suplementación con fitasa en dietas de gestación y lactancia sobre el rendimiento reproductivo, la digestibilidad aparente de tracto total (ATTD) del P, Ca y N en cerdas, y las características óseas de cerdas y lechones. Métodos: el Experimento 1 involucró 204 cerdas evaluadas en 3 centros de investigación norteamericanos. Las cerdas fueron asignadas a 1 de 4 tratamientos al momento del servicio: 1) Control negativo [dieta baja en Ca y P disponible (aP)], 2) Tratamiento 1 más 300 unidades de fitasa (FTU)/kg de dieta, 3) Tratamiento 1 más 600 FTU/kg de dieta, y 4) Control positivo (dieta con contenido normal de Ca y aP). En el Experimento 2, un total de 16 cerdas (Landrace × Yorkshire, de 2,3 partos en promedio) se asignaron al azar a 1 de 3 tratamientos en el d 34 a 52 de gestación, con base en su peso corporal (BW) y número de partos. Los tratamientos fueron: 1) dieta baja en Ca y aP, 2) dieta baja Ca y aP con 500 FTU de fitasa/kg de dieta, y 3) dieta con normal contenido de Ca y aP. Resultados: en el Experimento 1, el número de nacidos totales (p < 0,05), nacidos vivos (p = 0,05), peso de la camada de los nacidos vivos (p < 0,01), y cerdos destetados (p < 0.05) se incrementó cuadráticamente con la adición creciente de fitasa hasta el nivel de 300 FTU/kg. Hubo un aumento lineal en el peso al destete de los lechones (p < 0,05) al incrementar el nivel de fitasa. En el Experimento 2 no hubo diferencias en rendimiento reproductivo (p > 0,10). En gestación, la ATTD del P fue menor en el grupo de bajo Ca y aP sin fitasa que en el de normal Ca y aP (p < 0,01) y que en los grupos suplementados con fitasa (p < 0,05). La ATTD del Ca en el grupo de normal Ca y aP fue mayor que en el grupo de bajo Ca y aP sin fitasa (p < 0,05). En lactancia, el grupo suplementado con fitasa tuvo una mayor ATTD del P en comparación con los otros grupos (p < 0,05), mientras que la ATTD del Ca en el grupo suplementado con fitasa fue mayor que en el de bajo Ca y aP sin fitasa (p < 0,10). Cuando los datos de digestibilidad se agruparon para los períodos de gestación y lactancia, la ATTD del P en el grupo con fitasa fue la más alta entre los tratamientos dietarios (p < 0,05). No hubo efecto de la fitasa en el contenido de cenizas en hueso de las cerdas al destete ni en la resistencia ósea de los lechones o en las cenizas óseas al nacimiento. Sin embargo, los lechones de las cerdas suplementadas con fitasa tuvieron al destete mayor resistencia ósea (p < 0,10) y contenido de cenizas (p < 0,05) en comparación con los de las cerdas no suplementadas. Hubo correlaciones positivas al nacimiento entre el peso (BW) del lechón y su resistencia ósea (p < 0.01), y entre la resistencia ósea y su contenido de cenizas (p < 0,001). Además, se observaron correlaciones positivas al destete entre el BW del lechón y su contenido de ceniza en hueso (p < 0,05), entre el BW del lechón y su resistencia ósea (p < 0,001), y entre la resistencia y el contenido de cenizas óseas (p < 0,05). Conclusión: la suplementación con fitasa desde la mitad de la gestación y durante la lactancia aumentó la ATTD del P y Ca, en cerdas tanto gestantes como lactantes, mejoró la integridad ósea de la progenie, y mostró potencial para aumentar el tamaño y rendimiento de la camada, pero no afectó las características óseas de las cerdas ni de los recién nacidos. Palabras clave: características óseas, cerdos, disponibilidad de nutrientes, enzima exógena, fósforo. Resumo Antecedentes: a adição de fitasse na dieta de porcas pode melhorar a digestibilidade do P e Ca, assim como a integridade óssea dos leitões. Objetivo: Realizaram-se dois pesquisas para conferir o efeito da suplementação da fitasse em dietas para os períodos de gestação e lactação sobre o desempenho reprodutivo, a digestibilidade aparente no trato digestivo total (ATTD) de P, Ca e N em porcas, e as características ósseas de porcas e leitões. Métodos: o experimento 1 envolveu 204 porcas avaliadas em 3 centros de pesquisa dos Estados Unidos. As porcas foram designadas para um de quatro tratamentos no momento do serviço: 1) controle negativo [dieta baixa em Ca e P disponível (aP)], 2) Tratamento 1 mais de 300 unidades de fitasse (FTU) / kg de ração, 3) Tratamento 2, mais de 600 FTU / kg de ração, e 4) controle positivo (dieta com teor normal de Ca e aP). No Experimento 2, um total de 16 matrizes suínas (Landrace × Yorkshire, de 2,3 nascimentos em média) foram randomizados para 1 de 3 tratamentos nos dias 34-52 de gestação, com base no peso corporal (PC) e número de partos. Os tratamentos foram: 1) dieta pobre em Ca e Pd, 2) dieta pobre em Ca e aP com 500 FTU de fitasse / kg de ração, e 3) dieta com teor normal de Ca e aP. Resultados: no Experimento 1, o número de nascimentos totais (p < 0,05), nascidos vivos (p = 0,05), peso da leitegada de nascidos vivos (p < 0,01) e leitões desmamados (p < 0,05) aumentou quadraticamente com a adição crescente de fitasse no nível de 300 FTU / kg. Houve um aumento linear do peso ao desmame de leitões (p < 0,05) com os níveis crescentes de fitasse. No experimento 2, não houve diferença no desempenho reprodutivo (p > 0,10). Na gravidez, o ATTD de P foi menor no grupo de baixo Ca e aP sem fitasse do que no grupo Ca normal e aP (p < 0,01) e nos grupos de fitasse suplementado (p < 0,05). O ATTD de Ca no grupo normal de Ca e aP foi maior do que no grupo de baixo Ca e aP sem fitasse (p < 0,05). Na lactação, no grupo suplementado com fitasse apresentou um ATTD de P maior em relação aos outros grupos (p < 0,05), enquanto o ATTD de Ca do grupo suplementado com fitasse foi maior do que no grupo baixo de Ca e Pd e sem fitasse (p < 0,10). Quando os dados de digestibilidade foram agrupados para os períodos de gestação e lactação, a ATTD de P no grupo com fitasse foi maior entre os tratamentos dietéticos (p < 0,05). Não houve efeito da fitasse no teor de cinzas de osso de porcas ao desmame ou a força dos ossos ou cinzas ósseas dos leitões ao nascimento. No entanto, os leitões de porcas suplementadas com fitasse tiveram uma maior resistência óssea ao desmame (p < 0,10), e cinzas (p < 0,05) em comparação com as porcas não suplementadas. Houve correlação positiva entre peso (BW) ao nascimento do leitão e a resistência óssea (p < 0,01) e entre a força dos ossos e cinzas (p < 0,001). Além disso, foi observada uma correlação positiva entre o desmame dos leitões BW e teor de cinzas ósseas (p < 0,05), entre BW dos leitões e a resistência óssea (p < 0,001), e entre a resistência óssea e os conteúdos e cinza nos ossos (p < 0,05). Conclusão: a suplementação com fitasse na etapa media da gestação e durante a lactação aumentou a ATTD de P e Ca, tanto em porcas gestantes quanto lactantes, melhorou muito a integridade óssea da progênie, e mostrou potencial para aumentar o tamanho e desempenho da leitegada, mas não afetou as características ósseas das porcas nem dos leitões recém nascidos. Palavras chave: características ósseas, porcos, disponibilidade de nutrientes, enzimas exógenas, fósforo.